Treatment of hypertension in acute stage of myocardial infarction. Haemodynamic effects of labetalol. Issue 6 (June 1983) - Renard, M; Rivière, A; Jacobs, P; Bernard, R
Abstract : Labetalol was used to treat systemic hypertension (systolic blood pressure above 150 mmHg) in 11 patients with acute myocardial infarction; its haemodynamic effects and tolerance were studied. Increasing doses of labetalol were infused to lower systolic blood pressure to less than 130 mmHg; the optimal rate was then maintained for one hour (mean rate: 2.3 mg/min). Haemodynamic variables were measured before, during, and after labetalol infusion. Labetalol lowered blood pressure in all patients; this effect was related to a decrease both in total systemic resistance (17.7 to 14 IU) and in cardiac index (3.1 to 2.7 1/min per m2); the stroke index remained unchanged and the heart rate was reduced (94 to 81 beats/min). There was no significant change in the mean pulmonary wedge pressure; it was decreased, however, in the six patients with an initial pressure greater than 15 mmHg. The double product was greatly decreased (16 497 to 8598 mmHg x beats per min), which is favourable in acute myocardial infarction. We conclude that labetalol is a drug of choice to treat hypertension in acute myocardial infarction because it is very effective; its haemodynamic effects are likely to reduce myocardial oxygen requirements and suggest that labetalol administration does not worsen moderate left sided heart failure. The drug, however, may reduce the cardiac output.